Differential Impact of Severity and Duration of Status Epilepticus, Medical Countermeasures, and a Disease-Modifier, Saracatinib, on Brain Regions in the Rat Diisopropylfluorophosphate Model - Gage, Meghan; Putra, Marson; Gomez-Estrada, Crystal; Golden, Madison; Wachter, Logan; Gard, Megan; Thippeswamy, Thimmasettappa (Frontiers in Cellular Neuroscience, 2021)
Acute organophosphate (OP) toxicity poses a significant threat to both military and civilian personnel as it can lead to a variety of cholinergic symptoms including the development of status epilepticus (SE). Depending on its severity, SE can lead to a spectrum of neurological changes including neuroinflammation and neurodegeneration. In this study, we determined the impact of SE severity and duration on disease promoting parameters such as gliosis and neurodegeneration and the efficacy of a disease modifier, saracatinib (AZD0530), a Src/Fyn tyrosine kinase inhibitor. Animals were exposed to 4 mg/kg diisopropylfluorophosphate (DFP, s.c.) followed by medical countermeasures. We had five experimental groups: controls (no DFP), animals with no continuous convulsive seizures (CS), animals with 20-minutes continuous CS, 31-60-minutes continuous CS, and >60-minutes continuous CS. These groups were then assessed for astrogliosis, microgliosis, and neurodegeneration 8 days after DFP exposure. The 31-60-minutes and >60-minutes groups, but not 20-minutes group, had significantly upregulated gliosis and neurodegeneration in the hippocampus compared to controls. In the piriform cortex and amygdala, however, all three continuous CS groups had significant upregulation in both gliosis and neurodegeneration. In a separate cohort of animals that had 20 and >60-minutes of continuous CS, we administered saracatinib for 7 days beginning three hours after DFP. There was bodyweight loss and mortality irrespective of the initial SE severity and duration. However, in survived animals, saracatinib prevented spontaneous recurrent seizures (SRS) during the first week in both severity groups. In the 20-minutes CS group, compared to the vehicle, saracatinib significantly reduced neurodegeneration in the piriform cortex and amygdala. There were no significant differences in the measured parameters between the naïve control and saracatinib on its own (without DFP) groups. Overall, this study demonstrates the differential effects of the initial SE severity and duration on the localization of gliosis and neurodegeneration. We have also demonstrated the disease-modifying potential of saracatinib. However, its’ dosing regimen should be optimized based on initial severity and duration of CS during SE to maximize therapeutic effects and minimize toxicity in the DFP model as well as in other OP models such as soman.